ELECTRONIC-SPECTRUM OF THE AR-OH COMPLEX - EFFECT OF ISOTOPIC-SUBSTITUTION AND TEMPERATURE - Chakravarty, C; Clary, D (1990)
The spectrum of ArOD in the region of the OD (A 2Σ+, v=0) ← OD (X 2Π, v=0) electronic transition has been calculated at a temperature of 1.7 K using an ab initio potential energy surface. The calculated line positions, vibrational spacings and rotor constants are compared with experiment. The ArOH and ArOD spectra are also calculated at a temperature of 20 K and the hot band structure of the spectrum is discussed. © 1990.